# SOLUTION: Simplify or Perform operation : 113) (y2 – 16) / (-8 – 2y) 114) -2b^2 - 6b - 4 b^2 - 1 115) (

Algebra ->  Algebra  -> Expressions-with-variables -> SOLUTION: Simplify or Perform operation : 113) (y2 – 16) / (-8 – 2y) 114) -2b^2 - 6b - 4 b^2 - 1 115) (      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Expressions involving variables, substitution Solvers Lessons Answers archive Quiz In Depth

 Question 177889: Simplify or Perform operation : 113) (y2 – 16) / (-8 – 2y) 114) -2b^2 - 6b - 4 b^2 - 1 115) (3x – 6)/(x^2 – 4x + 4) 116) mx + 3x + my + 3y / m2 – 3m – 18 I'M SO COMPLETELY LOST!!! PLEASE HELP ME..... Answer by stanbon(57387)   (Show Source): You can put this solution on YOUR website!Simplify or Perform operation : 113) (y^2 – 16) / (-8 – 2y) Factor where you can to get: [(y-4)(y+4)] / [-2(4+y)] Cancel the y+4 common factor to get: (y-4)/(-2) ========================= 114) (-2b^2 - 6b - 4) / (b^2 - 1) Factor where you can to get: [-2(b^2 + 3b +2)] / [(b-1)(b+1)] Factor again: = [-2(b^2 + 3b +2)] / [(b-1)(b+1)]] = [-2(b+1)(b+2)] / [(b-1)(b+1)] Cancel the b+1 common factor to get: = [-2(b+2)] / [(b-1)] ============================== 115) (3x – 6)/(x^2 – 4x + 4) Factor to get: (3(x-2)) / [(x-2)(x-2)] Cancel the common x-2 factor: = 3/(x-2) ======================== 116) mx + 3x + my + 3y / m^2 – 3m – 18 Factor to get: [m(x+y) + 3(x+y)] / [(m-6)(m+3)] Factor again: [(x+y)(m+3)] / [(m-6)(m+3)] Cancel the common factor to get: (x+y) / (m-6) ======================== Cheers, Stan H.